International Trade with Higher Education Services and Economic Growth in Central and Eastern Europe - Ana Mihei (CES Working Papers, 2013)
The higher education international market is currently in a continuous development. In this article, we have analyzed the statistical data in order to determine Central and Eastern European countries' flows of higher education. The aim was to see to which extent these countries are involved in international trade with higher education services, as well as the impact that this trade has on national economies. We have also tried to determine the conditions that would make these states benefit more due to educational flows.
Keywords: I29; N70; 330; higher education; international trade; Central and Eastern Europe Romania